Dampak Pariwisata Terhadap Kondisi Sosial Ekonomi Di Taman Mini Indonesia Indah pada Era New Normal - Rafitra Amira Putri; Liliana Dewi; Ines Windyarti; Alya Farika; Yasmin Nur Sya’ban (Jurnal Syntax Transformation, 2021)
According to Law no. 10 of 2009 concerning Tourism, Tourism is a variety of tourist activities and is supported by various facilities and services provided by the community, businessmen, government and local governments. One of the tourism areas that Indonesia has is Taman Mini Indonesia Indah Tourism. During the current pandemic, the level of tourism visits in Indonesia, especially in the Taman Mini Indonesia Indah tour, has decreased quite significantly. This study aims to determine how the economic impact on the Taman Mini Indonesia Indah Tourism Object, to know the comparison of the income of traders before and after the New Normal Era at Taman Mini Indonesia Indah Tourism Object, and to find out who is affected by the economy at the Taman Mini Indonesia Indah Tourism Object. The method used is a qualitative and quantitative approach (Mix Method). Quantitative data were obtained through questionnaires and qualitative data were obtained through in-depth interviews using interview guides and field observations. Techniques in determining research respondents using cluster accidental sampling. The results showed that most of the employees and traders in the Taman Mini Indonesia Indah tour experienced an economic decline.